Subpicosecond colliding pulse mode locking at 126 GHz in monolithic GaAs/AlGaAs quantum well lasers: Experiments and theory - Tandoi, G.; Javaloyes, J.; Avrutin, E.; Ironside, Charlie; Marsh, J. (2013)
In this paper, we present results from monolithic passively mode-locked GaAs/AlGaAs quantum well lasers operating at 830 nm. Colliding pulse mode locking is achieved at repetition rates of 126 GHz with pulsewidths as short as 0.43 ps, an unprecedented value in monolithic semiconductor lasers operating at such high pulse repetition rates. We use a double quantum well laser epistructure with larger mode size d/G (d is the quantum well thickness and G is the optical confinement) and investigate the effect of the saturable absorber length on the mode-locking operation. The experimental results are theoretically explained and reproduced using a traveling wave model with an improved time-domain response for both the gain and the absorber sections of the device. The model confirms that the thermally induced spectral detuning of the absorber relative to the gain section determines both the optimal absorber length and the optimal biasing conditions to achieve the shortest pulse duration and highest peak power. © 1995-2012 IEEE.